Visual Dysfunction in Chinese Children With Developmental Dyslexia: Magnocellular-Dorsal Pathway Deficit or Noise Exclusion Deficit? - Ji, Yuzhu; Bi, Hong-Yan (Frontiers in Psychology, 2020)
Many studies have suggested that children with developmental dyslexia (DD) not only show phonological deficit but also have difficulties in visual processing, especially in nonalphabetic languages such as Chinese. However, mechanisms underlying this impairment in vision are still unclear. Visual magnocellular deficit theory suggests that the difficulties in the visual processing of dyslexia are caused by the dysfunction of the magnocellular system. However, some researchers have pointed out that previous studies supporting the magnocellular theory did not control for the role of “noise.” The visual processing difficulties of dyslexia might be related to the noise exclusion deficit. The present study aims to examine these two possible explanations via two experiments. In experiment 1, we recruited 26 Chinese children with DD and 26 chronological age–matched controls (CA) from grades 3 to 5. We compared the Gabor contrast sensitivity between the two groups in high-noise and low-noise conditions. Results showed a significant between-group difference in contrast sensitivity in only the high-noise condition. In experiment 2, we recruited another 29 DD and 29 CA and compared the coherent motion/form sensitivity in the high- and low-noise conditions. Results also showed that DD exhibited lower coherent motion and form sensitivities than CA in the high-noise condition, whereas no evidence was observed that the group difference was significant in the low-noise condition. These results suggest that Chinese children with dyslexia have noise exclusion deficit, supporting the noise exclusion hypothesis. The present study provides evidence for revealing the visual dysfunction of dyslexia from the Chinese perspective. The nature of the perceptual noise exclusion and the relationship between the two theoretical hypotheses are discussed.